Study on low and high strain rate behaviour of the adhesive bonds for armour application. Issue 1 (11th March 2020) - Ahmed, A.; Chouhan, H.; Kartikeya, K.; Bhatnagar, N.
ABSTRACT: Adhesives are viscoelastic polymeric materials with rate-dependent behaviour. A personal body armour for higher threat perception consists of hard ceramic facing adhesively joined to a composite laminate backing. This work focuses on the mechanical testing of two types of adhesive materials, i.e ., epoxy-based and polyurethane-based by bonding dissimilar materials to understand their role in protection against ballistic impact. Block shear tests were conducted for two types of adhesive at various thicknesses of adhesives layer. Epoxy-based adhesive showed higher shear strength than polyurethanes-based adhesive. Optimal thickness for each adhesive under shear loading was also determined from these tests. Split Hopkinson pressure bar tests were conducted to understand the compressive behaviour of adhesives at higher strain rates in order to simulate the high-velocity projectile impacts.